Mindset of employees working in a matrix organizational structure - Lukinaitė, Eglė; Sondaitė, Jolanta (Business: Theory and Practice, 2017)
Organizations wishing to be successful and control their complexity will probably have to develop matrix mindset. The main goal of this research is to reveal the mindset of employees working in a matrix organizational structure. The data were collected through focus groups. A thematic analysis was employed to achieve the goal. The results revealed that employees working in a matrix organizational structure perceive their influence through cooperation, discussion and personal efficiency. Employees not working in a matrix organizational structure emphasize the manager’s influence and formal power instead of their own personal power.